On the interaction of the modified FM signal with frequency-selective devices - Рязанцев, О.В.; Кулик, М.В.; Съянов, А.М. (Radiotekhnika, 2012)
The basic parameters of the FM signal with ±π/2 phase inset are analyzed and the optimal conditions of its release using frequency-selective devices are defined.